The Evolving Role of Endoscopy in Revisional Metabolic and Bariatric Surgery - Rieske, Richard R.; Ardila-Gatas, Jessica (Digestive Disease Interventions, 2024)
The obesity epidemic continues to be a global health concern impacting over 890 million adults worldwide. These numbers have quadrupled since 1990, and global health surveys estimate another 2.5 billion adults are overweight. The disease of obesity is chronic in nature and difficult to treat. The number of metabolic and bariatric surgeries performed today continues to increase and with it the number of revisional surgeries and management of complications. Upper gastrointestinal endoscopy has played an important role in diagnosing and managing patients with obesity. Endoscopy is a safe and minimally invasive technique to address surgical complications and explore new techniques for the management of obesity. In this article, we aim to review the evolving role of endoscopy in revisional bariatric surgery: management of immediate complications, including bleeding, strictures, leaks, and erosion of bands; techniques to access the gastric remnant after a gastric bypass; and management of weight regain.
Keywords: bariatric surgery; endoscopic therapy; weight loss complications